Selection of electrode tips for the resistance spot welding of dissimilar stainless steels - Khuenkaew Teerawut; Kanlayasiri Kannachai (MATEC Web of Conferences, 2018)
This research sought to resolve the issue of electrode tip selection used in the resistance spot welding for two different stainless steel grades under otherwise identical welding parameters: SUS316 and SUS425. The study used a full fractional design in order to perform the analysis of the variables involved, while the quality of the weld was assessed by considering the indentation depth, penetration, and nugget diameter. The results of the study described the nugget diameter and penetration for all welds with the various different electrode tips which met the specified requirements of the customers. A single type of upper R30 and lower R30 electrodes achieved acceptable indentation depth. Ideally, good weld quality would demand a large nugget diameter, shallow indentation, and good penetration, all contribution to an acceptable overall appearance. Both R30 electrode tips are able to achieve the desired quality requirements in the spot welding process.